2013
DOI: 10.1038/jp.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine collaboration improves perinatal regionalization and lowers statewide infant mortality

Abstract: OBJECTIVES We assessed a telemedicine (TM) network's effects on decreasing deliveries of very low birth-weight (VLBW, <1500 grams) neonates in hospitals without Neonatal Intensive Care Units (NICUs) and statewide infant mortality. STUDY DESIGN This prospective study used obstetrical and neonatal interventions through TM consults, education, and census rounds with 9 hospitals from July 1, 2009 – March 31, 2010. Using a generalized linear model, Medicaid data compared VLBW birth sites, mortality, and morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…This resource-intensive model, relying on videoconferencing between obstetrical and neonatal teams, significantly reduced the deliveries of very-low-birth-weight infants in nine participating hospitals without NICUs from 13.1 to 7.0% (94). This finding is important because the researchers simultaneously found a concurrent and statistically significant reduction in statewide infant mortality.…”
Section: Perinatal and Newborn Carementioning
confidence: 53%
See 1 more Smart Citation
“…This resource-intensive model, relying on videoconferencing between obstetrical and neonatal teams, significantly reduced the deliveries of very-low-birth-weight infants in nine participating hospitals without NICUs from 13.1 to 7.0% (94). This finding is important because the researchers simultaneously found a concurrent and statistically significant reduction in statewide infant mortality.…”
Section: Perinatal and Newborn Carementioning
confidence: 53%
“…In Arkansas, telemedicine-supported care in the rural setting has been shown to reduce the need for in-person visits (where the mother would have to travel to the tertiary center) by nearly 50%, while maintaining the appropriate utilization of maternal-fetal medicine subspecialty consultations (91). Studies evaluating the use of antenatal management using telemedicine have found that collaborations between a subspecialty perinatal referral hospital, and hospitals lacking neonatologists successfully reduced the number and proportion of very-low-birth-weight births at these facilities (93,94). With regard to fetal telecardiology, other researchers have demonstrated that remote diagnostic evaluations and parental counseling can be done accurately and are well accepted by providers and families (95)(96)(97).…”
Section: Perinatal and Newborn Carementioning
confidence: 99%
“…[3][4][5][6] A few studies have demonstrated the value of telemedicine in pediatric and neonatal critical care. 7,8 One study in particular demonstrated that an infrastructure for telemedicine consultation and collaboration decreased very low birth weight deliveries at hospitals without a NICU and was associated with decreased statewide infant mortality. However, very little is known about the role of telemedicine in neonatal resuscitation.…”
Section: Introductionmentioning
confidence: 98%
“…9,10 In 2013, Kim et al 10 found that an infrastructure for perinatal telemedicine consultation and collaboration decreased very low-birth-weight deliveries at hospitals without a NICU and was associated with decreased statewide infant mortality. When general pediatric providers had real-time audiovisual communication with a neonatologist during simulated neonatal resuscitations, the time to effective ventilation (the most important intervention in newborn resuscitation) was significantly reduced.…”
mentioning
confidence: 99%